Peningkatan Jiwa Kewirausahaan Bagi Peserta Didik Unit Pelayanan Sosial Bina Remaja Radin Intan Bandar Lampung - Hafiz, Aliy; Dwi Ladista, Rindy; Maryani, Ani (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2024)
Entrepreneurial spirit is very important because it can help improve the quality of life of the community by creating high-quality products and services. Entrepreneurial spirit also helps improve community welfare and increase economic welfare. Entrepreneurial spirit is instilled from an early age because it can help someone become a more independent person, think creatively and progressively. This community service activity is carried out to foster an independent entrepreneurial spirit for Students at the Radin Intan Youth Social Service Unit (PSBR), Bandar Lampung. The implementation of this community service activity is through 3 (three) stages, namely the preparation stage, the activity implementation stage, and the evaluation stage. This activity uses a lecture method, including discussions on technopreneurship, Entrepreneurship in the Digital Era, E-Commerce where participants carry out simulations using cellphones. The results of this activity are that students are expected to be able to provide increased abilities and motivation for learning participants to utilize technology in student business activities where students are able to manage e-commerce accounts, manage business WA and manage digital marketing with social media